3D Geophysical and Geological Modeling of the South Orkney Microcontinent (Antarctica): Tectonic Implications for the Scotia Arc Development. Issue 4 (11th April 2023) - Morales‐Ocaña, Cecilia; Bohoyo, Fernando; Escutia, Carlota; Marín‐Lechado, Carlos; Rey‐Moral, Carmen; Druet, María; Galindo‐Zaldívar, Jesús; Maestro, Adolfo
Abstract: The opening of the Scotia Arc resulted in the final breakup of the land bridge between South America and the Antarctic Peninsula. The South Orkney Microcontinent (SOM) constituted part of this former connection and it is now the largest continental block in the Southern Scotia Arc. We present the first 3D model of the SOM that, given its strategic position and characteristics, allows us to advance the knowledge of the tectonic processes involved in the development of the Scotia Arc. Due to the scarcity of reliable geological data, the initial approximation of the deep structure of the SOM was supported by the calculation of three main geological boundaries from geophysical data: the acoustic basement, the boundary of the magnetic anomaly source and the Moho depth. The 3D model was built, refined and validated by forward modeling and joint inversion of gravity and magnetic data. We have accurately defined the geometry of the sedimentary cover, determined the geometry of the intrusive igneous body causing the Pacific Margin Anomaly (PMA) and mapped the heterogeneity of the crustal thickness. These structural features show a clear relationship to each other and are consistent with an important E‐W extension to the east of the SOM during early stages of the Scotia Arc formation, prior to the opening of the Powell Basin. Key Points: 3D modeling outlines the geometry of the sedimentary basins, intrusive igneous body and Moho in the South Orkney Microcontinent Modeled deformation is coherent with strong extension east of the Microcontinent during the early stages of the Scotia Arc formation Extension migrated westwards causing the opening and oceanization of the Powell Basin